Autophagy‐Mediated Degradation of IAPs and c‐FLIPL Potentiates Apoptosis Induced by Combination of TRAIL and Chal‐24. Issue 5 (2nd November 2015) - Xu, Jennings; Xu, Xiuling; Shi, Shaoqing; Wang, Qiong; Saxton, Bryanna; He, Weiyang; Gou, Xin; Jang, Jun‐Ho; Nyunoya, Toru; Wang, Xia; Xing, Chengguo; Zhang, Lin; et al.
ABSTRACT: Combination chemotherapy is an effective strategy for increasing anticancer efficacy, reducing side effects and alleviating drug resistance. Here we report that combination of the recently identified novel chalcone derivative, chalcone‐24 (Chal‐24), and TNF‐related apoptosis‐inducing ligand (TRAIL) significantly increases cytotoxicity in lung cancer cells. Chal‐24 treatment significantly enhanced TRAIL‐induced activation of caspase‐8 and caspase‐3, and the cytotoxicity induced by combination of these agents was effectively suppressed by the pan‐caspase inhibitor z‐VAD‐fmk. Chal‐24 and TRAIL combination suppressed expression of cellular FLICE (FADD‐like IL‐1β‐converting enzyme)‐inhibitory protein large (c‐FLIPL ) and cellular inhibitor of apoptosis proteins (c‐IAPs), and ectopic expression of c‐FLIPL and c‐IAPs inhibited the potentiated cytotoxicity. In addition, TRAIL and Chal‐24 cooperatively activated autophagy. Suppression of autophagy effectively attenuated cytotoxicity induced by Chal‐24 and TRAIL combination, which was associated with attenuation of c‐FLIPL and c‐IAPs degradation. Altogether, these results suggest that Chal‐24 potentiates the anticancer activity of TRAIL through autophagy‐mediated degradation of c‐FLIPL and c‐IAPs, and that combination of Chal‐24 and TRAIL could be an effective approach in improving chemotherapy efficacy. J. Cell. Biochem. 117: 1136–1144, 2016. © 2015 Wiley Periodicals, Inc.